2016
DOI: 10.26417/ejes.v4i1.p73-78
|View full text |Cite
|
Sign up to set email alerts
|

Application of Quality Management System in Tourism Sector in Kosovo

Abstract: Tourism is one of the most complex activities of today's modern society. In developed countries and in some other countries in transition, it presents a significant product of export and employment generator. The increase of the quality of service and application of the quality management system in tourism industry is undoubtedly a challenge that we are all interested to deal with. Quality Management of Services is directly connected with training and qualification of human resources involved in this sector. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In other research, Brătucu et al [65] demonstrated that most hotel managers are concerned with issues linked to sustainable development of the accommodation unit they manage, but, at the same time, the researchers noticed a low interest in sustainable evolution negatively correlated with the comfort level of the accommodation unit. Also, there are a number of researchers who identified the existence of a link between the implementation of quality standards and the increase of hotel performance, but could not prove the existing causal relationships [66,67].…”
Section: Resultsmentioning
confidence: 99%
“…In other research, Brătucu et al [65] demonstrated that most hotel managers are concerned with issues linked to sustainable development of the accommodation unit they manage, but, at the same time, the researchers noticed a low interest in sustainable evolution negatively correlated with the comfort level of the accommodation unit. Also, there are a number of researchers who identified the existence of a link between the implementation of quality standards and the increase of hotel performance, but could not prove the existing causal relationships [66,67].…”
Section: Resultsmentioning
confidence: 99%